Modelling of reactor CPS cooling circuit voiding - Narimantas Listopadskis; Raimondas Pabarčius; Aurimas Tonkūnas (Lietuvos Matematikos Rinkinys)
Modelling of Ignalina NPP RBMK-1500 reactor control and protection system cooling circuit (CPSCC) voiding logic, which was implemented in code QUABOX/CUBBOX-HYCA, is described. Analysis of numerical simulation results shows, that this logic is correct, the results are comparable to analogous modelling data obtained by Russian code STEPAN/KOBRA. The improved QUABOX/CUBBOX-HYCA code version allows to simulate the CPSCC voiding for RBMK-1500 reactor operation at any power level. Together with implemented and validated full CPS operation logic it could be used for simulation of various transitional processes, which can occur in nuclear reactors of Ignalina NPP, or during analyses when the safety substantiation of reactor unit operation is performed.